Pengaruh Kompetensi Manajerial Kepala Sekolah dan Kompetensi Guru Terhadap Mutu Pendidikan (Study SMP IT Ar-Raudhah dan SMP IT Bismilah) - Abdul Latif; Agus Gunawan; Atang Suryana (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study to find out whether Influence the Managerial Competence of the Principal and the Competence of Teachers on the Quality of Education in the Integrated Islamic Junior High School Bismillah and the Integrated Islamic Junior High School Arraudoh. The research method used Quantitative Research a Correlation approach, the population is 50 people, the sample used is the entire population. The results of the study were simultaneously obtained F calculate > F table (211.43 > 3,190) thus Ha was accepted and H0 was rejected, which means the hypothesis is accepted and there is a significant influence between X1 and X2 on Y by 65.3%. Between the two schools shows the Influence of The Principal's X1 on Y in Arraudoh Integrated Islamic Junior High School 39.3%, Bismillah Integrated Islamic Junior High School 67.8%. The Influence of X2 on Y of Integrated Islamic Junior High School Education Arraudoh 53.5%, Integrated Islamic Junior High School Bismillah 26.1%. Influence of X1 and X2 on Y of Education in Integrated Islamic Junior High Schools) Arraudoh 92.8% Integrated Islamic Junior High School) Bismillah 93.9%.